Impregnated charcoal cloth for the treatment of air polluted with hydrogen cyanide. Issue 3 (24th September 2012) - Prasad, G.K.; Kumar, J. Praveen; Ramacharyulu, P.V.R.K.; Singh, Beer
<x xml:space="preserve">Abstract</x> Impregnated charcoal cloth was prepared by a novel single‐step method using water‐soluble salts such as copper nitrate, silver nitrate, and ammonium heptamolybdate. Impregnation was achieved by using simple, user‐friendly spraying technique. The obtained cloth samples were characterized by nitrogen adsorption technique. Kinetics of hydrogen cyanide adsorption were explored using charcoal cloth impregnated with copper(II), molybdenum(VI), and silver(I) salts. Modified Wheeler equation was used for analyzing adsorption kinetics, and the data were represented as kinetic saturation capacity and kinetic rate constant. Kinetic saturation capacity value was found to decrease from 0.01 to 0.003 g/g as the value of inlet concentration increased from 81 to 365 ppm. Kinetic rate constant value increased from 2018 to 5048 min−1 when the flow rate was increased from 400 to 1000 mL/min, whereas kinetic saturation capacity value was found to be invariant. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 715–720, 2013